The Challenge of Minority Integration. Politics and Policies in the Nordic Nations - Kivisto, Peter; Kraus, Peter A. (De Gruyter, 2015)
How is solidarity achieved in highly diverse societies - particularly those that have been until recently characterized by rather homogeneous populations? What are the implications of growing levels of diversity on existing social arrangements? These two fundamental questions are explored in this edited collection, which examines the challenges of minority integration in four Nordic countries: Denmark, Finland, Norway, and Sweden. These nations represent paradigmatic examples of social democratic welfare states that place a premium on a robust package of social rights, combined with policies aimed at reducing levels of class-based inequality and promoting gender equity. All four of these nations have witnessed growing levels of diversity due to immigration and three of them have been forced to rethink their policies concerning the indigenous Sámi, as well as old minority groups. Two introductory chapters, by Thomas Hylland Eriksen and Peter Kivisto, serve as a conceptual framework for the seven case studies that follow, and which, from a variety of perspectives and with differing emphases, analyze the evolving realities in these nations today. Taken together, they offer evidence of the critical issues surrounding attempts to achieve solidarity while valorizing diversity.
English
Keywords: diversity; Nordic countries; minorities; integration; solidarity